2021
DOI: 10.3390/ma14185184
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Shear Interface Response of Hybrid Thin CFRP–Concrete Slabs

Abstract: Hybrid slabs made of carbon-fiber-reinforced polymer (CFRP) and concrete provide a solution that takes advantage of the strength properties of both materials. The performance of the system strongly depends on the CFRP–concrete interaction. This study investigates the shear behavior in the interface of the two materials. Eight full-scale experiments were carried out to characterize the interface shear response of these hybrid elements using different connection solutions. An untreated surface is compared to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This observation proved the effectiveness of the FRP-FRP and FRP-FRCM connections proposed in this novel technology and turned the analysis far from the FRP-concrete connection typically analyzed for current hybrid structures (see, for example, the large plastic bolt deformations found in the load–slip curves by Di et al [ 27 ] and Rajchel et al [ 28 ] or the load–slip curves of FRP form-concrete elements by Gong et al [ 29 ]). Finally, comparing the experimental observations of HP1 tests with the idealization of the shear behavior of the FRP-flexible mesh-concrete connection presented in [ 16 ], which is the closest case to the novel tested technology, it is concluded that the FRP-FRCM connection worked in the elastic range during all tests of the HP1 specimen.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This observation proved the effectiveness of the FRP-FRP and FRP-FRCM connections proposed in this novel technology and turned the analysis far from the FRP-concrete connection typically analyzed for current hybrid structures (see, for example, the large plastic bolt deformations found in the load–slip curves by Di et al [ 27 ] and Rajchel et al [ 28 ] or the load–slip curves of FRP form-concrete elements by Gong et al [ 29 ]). Finally, comparing the experimental observations of HP1 tests with the idealization of the shear behavior of the FRP-flexible mesh-concrete connection presented in [ 16 ], which is the closest case to the novel tested technology, it is concluded that the FRP-FRCM connection worked in the elastic range during all tests of the HP1 specimen.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the fatigue behavior of pultruded FRP profiles with bolted joints and epoxy resin joints was studied by Wingerde et al [ 14 ]. A novel approach to dealing with FRP-concrete connections has been recently proposed by Mahboob et al [ 15 , 16 ], who used epoxy resin to connect a flexible fiber fabric to carbon FRP parts and left the free parts of this fabric embedded in concrete, resulting in a ductile and superficially distributed FRP-concrete connection. The fabric used was analogous to the one used in FRCM systems.…”
Section: Introductionmentioning
confidence: 99%
“…The first use of fiber reinforced polymer dated back thirty years ago, and nowadays, FRP material is employed by many engineers, technician and architects in order to strengthen and reinforce concrete structures [ 1 , 2 , 3 , 4 , 5 ]. Recently, there is a great interest on the applications of FRP profiles to produce hybrid structural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcing and strengthening of concrete members leads to increased flexural capacity [3]. Many researchers have studied the behavior of concrete members that were reinforced and strengthened with FRP [4,5]. Among these works, Sami [6] tested concrete slabs bonded with a composite externally and he saw a significant increase in flexural capacity.…”
Section: Introductionmentioning
confidence: 99%